Individualization of psychological training and its importance at different stages of many years’ perfection in tennis - Vysochina, N.L.; Makuts, T.B. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: to determine significance of individualized approach during psychological training at different stages of many years’ perfection in tennis. The tasks of the research were studying of place and role of psychological component in general system of tennis players’ sport training as well as determination of specificities of individualized approach during 14-15 years old and elite tennis players’ psychological training. Material: In the research 24 experts, coaches of combined teams and clubs, elite tennis players took part. Results: Role of psychological training in general system of many years’ perfection has been determined. We also found out that individualization of psychological training in modern tennis is not paid sufficient attention to at present. Most of the questioned respondents pointed, that such training is conducted mainly with elite sportsmen (42%). Only 14% noted that individual psychological training is carried out at basic stages of many years’ perfection. Conclusions: Principle of individualization is a determining one in the course of sportsmen’s training at stages of many years’ perfection. About 86% of experts stressed on significance of application of individualized approach in work with tennis players. Consideration of tennis players’ individual features during psychological training is a compulsory matter in increasing of effectiveness of sportsmen’s training and competition functioning.